2021
DOI: 10.1002/ehf2.13247
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of left ventricular longitudinal systolic function parameters in the prediction of adverse outcome in heart failure with preserved ejection fraction

Abstract: Aims Several different diagnostic parameters can be used to assess left ventricular (LV) longitudinal systolic function, but no studies comparing their predictive value have been conducted. We sought to compare the prognostic value of LV long-axis function parameters at rest and exercise using the population with heart failure with preserved ejection fraction (HFpEF). Methods and results Clinical and biochemical variables were collected at baseline in 201 patients with HFpEF. Echocardiography was performed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
(86 reference statements)
1
10
0
Order By: Relevance
“…In 9 studies, variables such as age, sex, race, history of CV disease, medication history, laboratory tests, and others that might affect the association between LV GLS and research outcomes were adjusted (Table 3). Meta-analyzes with random-effects models showed that the low LV GLS values in HFpEF patients were associated with a higher risk of all-cause death (HR: 1.12; 95% CI: 1.01-1.25; p=0.000, I 2 =84%; P = 0.031)[29,42,44,47,49,51] (Fig 4A), but not with the composite outcomes (all-cause death and HF hospitalization (HR: 1.03; 95% CI: 0.95-1.11; p=0.000, I 2 = 83%; P = 0.51)[29,4548,51,52] (Fig 4B) or CV death and HF hospitalization (HR: 1.04; 95% CI: 0.94-1.14; p=0.000, I 2 = 81%; P = 0.49)) [6,28,37,41,43] (Fig 4C)). Additionally, three studies by Xu et al, Freed et al, and Kosmala et al reported no association between low LV GLS values in HFpEF patients and the composite outcome of all-cause death and CV hospitalization [40,50,53].…”
Section: Resultsmentioning
confidence: 99%
“…In 9 studies, variables such as age, sex, race, history of CV disease, medication history, laboratory tests, and others that might affect the association between LV GLS and research outcomes were adjusted (Table 3). Meta-analyzes with random-effects models showed that the low LV GLS values in HFpEF patients were associated with a higher risk of all-cause death (HR: 1.12; 95% CI: 1.01-1.25; p=0.000, I 2 =84%; P = 0.031)[29,42,44,47,49,51] (Fig 4A), but not with the composite outcomes (all-cause death and HF hospitalization (HR: 1.03; 95% CI: 0.95-1.11; p=0.000, I 2 = 83%; P = 0.51)[29,4548,51,52] (Fig 4B) or CV death and HF hospitalization (HR: 1.04; 95% CI: 0.94-1.14; p=0.000, I 2 = 81%; P = 0.49)) [6,28,37,41,43] (Fig 4C)). Additionally, three studies by Xu et al, Freed et al, and Kosmala et al reported no association between low LV GLS values in HFpEF patients and the composite outcome of all-cause death and CV hospitalization [40,50,53].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, we have evaluated the prognostic value of GLS at rest, which does not allow to unmask a decrease in GLS at exercise, an important feature of HFPEF syndrome [20,21]. This was well demonstrated by Wang, et al who found a signi icant association between the GLS of effort, and not of rest, with CV events [22] and by Gozdzik, et al in a recent Australian study [23] Table 4.…”
Section: Prognostic Relevance Of Impaired Gls In Hfpefmentioning
confidence: 98%
“…As already mentioned, the data for heart failure pharmacotherapy in HFpEF are so far very limited, and no trial has achieved convincing morbidity/mortality endpoints to date. This probably reflects the disease complexity, as there are multiple pathophysiologic mechanisms in HFpEF, such as impaired diastolic function and impaired systolic reserve, impaired longitudinal ventricular systolic and atrial function, impaired autonomic heart function, and peripheral mechanisms such as endothelial and skeletal muscle dysfunction [ 6 , 10 13 ]. Now, the question is: “How should we treat patients with DHFpEF?”…”
Section: Diabetic Heart Failure With Preserved Ejection Fraction As A...mentioning
confidence: 99%